IMPACT OF INFORMATION TECHNOLOGY ON THE STRUCTURE OF MATHEMATICAL ABILITIES OF HIGH SCHOOL STUDENTS OF MATHEMATICAL PROFILE - E. V. Emelianova (Acta Biomedica Scientifica, 2015)
We relied on the structure of V.A. Krutetskiy consisting of four components: obtaining mathematical information (perceptual component); processing mathematical information (procedural component); storage of mathematical information (mnemonic component); mathematical orientation of the mind (general synthetic component). The following hypothesis was proposed: the use of information technology affects the positive trend in the development of all components of mathematical abilities, and especially on general synthetic component due to the harmonious combination of two sub-components: verbal-logical and visual-figurative. We used a modified methodic, which is a shortened version of tasks classification of V.A. Krutetskiy. The tasks consisted of nine batteries of problems whose solution was assessed by a dichotomous scale, and then the result is expressed as a percentage by number of correctly solved tasks in the series. Analysis of the results of the comparison of mathematical abilities in a sample of 60 people (students-programmers and students non-programmers) showed that a high school students-programmers developed a general synthetic component (t = 2,566, p = 0,013). The students perform tasks with the visual representations and schemes better that contributes to the development of parameters procedural component.